Biochemical evaluation of chilli (Capsicum annuum L) cultivars suitable for export - T Vijayalakshmi, P Venkata Reddy, K Uma Jyothi, S Surya Kumari, K V Siva Reddy, (Journal of Spices and Aromatic Crops, 2008)
Chilli, an important spice of India is cultivated in all the states and Union territories of thecountry. Some varieties are famous for typical red colour and others are known for pungency.A study was conducted on biochemical constituents viz., oleoresin, capsanthin and capsaicinfor two consecutive years viz; 2005-06 and 2006-07.Twenty three cultivars collected from thecoordinated centres of All India Co-ordinated Vegetable Improvement Project from all overthe country were used in this study. Among the cultivars studied, PC-7 and PC-6 fromPantnagar recorded the highest colour value of 50782 and 49456 EOA colour value respectivelyand the lowest colour value was recorded by DCL-352(19932 EOA colour value) . The highestoleoresin content was recorded by DCL 352 (13.82%) of IARI and the lowest was recorded byPC-7 (6.91%). The capsaicin content among the entries was in the range of 0.256 % (SKAU-C-101) to 0.528% (BC-40-2). From the above study, it was concluded that the cultivars viz;PC-7, PC-6 of Pantnagar and Sel 11 of Ludhiana had high colour value and similarly BC-40-2 of Bhubaneshwar had high pungency and suitable to catch high market price both indomestic and export market